Penerapan Model Pembelajaran Project Based Learning terhadap Kreativitas Siswa PJOK di Kelas VI SD Negeri 37 Pekanbaru - Shinta Kesuma Aji; Ramadi, Ramadi; Hidayat, Hirja (Universitas Hamzanwadi, 2024)
This study aims to improve student creativity in learning PJOK by applying a project-based learning (PJBL) model using the mind mapping project method. The problem of the lack of effectiveness of the application of learning media and the lack of student involvement in PJOK learning activities in the classroom. This research uses the PTK method. Data collection was done through observation, documentation, field notes, learning instruments and observation sheets. The data obtained were analyzed using quantitative and qualitative analysis techniques. Quantitative analysis to calculate the percentage of student creativity, while qualitative analysis based on observations during the learning process. The results showed a significant increase in student creativity from Cycle I to Cycle II. The percentage of teacher activity increased significantly from 82.1% in Cycle I to 92.8% in Cycle II. While the percentage of student creativity increased from 71.8% in Cycle I to 84.3% in Cycle II. Through the implementation of the PPA model with the mind mapping project method, students are more actively involved in learning, provide creative ideas, and complete the project better. This research makes an important contribution in enriching learning practices, promoting student engagement, and improving the effectiveness of PJOK learning.